EKSISTENSI MADRASAH DALAM SISTEM PENDIDIKAN NASIONAL - Sultan; Ina Damayanti (Fakultas Agama Islam Universitas Cokroaminoto Makassar, 2022)
The research aims to analyze madrasah in the national education system. The type of research used is library research, with a research approach namely the sociological approach to education and the normative theological approach. The results of the study show that along with the development and expansion of Islam, madrasas as Islamic educational institutions began to be established and developed in the Islamic world around the 5th-6th century H or 11-12th centuries. So madrasas need serious renewal to overcome and educate the nation's children who are not only fixated on old-style study benches but are also able to compete in a world full of